Methodology of studying professional value orientations of medical university students - Murzina, O. A.; Makyeyeva, L. V.; Pototska, O. I.; Raznatovska, O. M.; Мурзіна, Олена Анатоліївна; Макєєва, Людмила Валеріївна; Потоцька, Олена Іванівна; Разнатовська, Олена Миколаївна (Australia - Melbourne, 2021)
Abstract. The article presents a methodology of studying the professional value orientation of future doctors. The analysis of the applied theoretical scientific and methodical apparatus revealed that the existing approaches in pedagogy laid the theoretical foundations for the consideration of professional and value orientations of the individual as a system that motivates and regulates human activity. The study of the peculiarities of the medical profession from the axiological point of view showed that the professional value orientations of the future doctor include both universal and professional values associated with the content of the medical profession, its content, focus and purpose.
Keywords: values; value orientations; square of values